O auto-emprego no Brasil: uma análise dos fatores determinantes - Gomes, Rodrigo Campos (2009)
The aim of this dissertation is to analyze the determinants and recent dynamics of self-employment in Brazil, taking as a starting point similar analysis carried out by developed countries. The methods of research consist of bibliographical research, providing the required theoretical basis, and analysis of the main sources of information over the labor market in Brazil. Among the data sources used in this work, the PME and the PNAD are highlighted, remaining in line with the main definitions of major international organizations, such as ILO. The own-account workers are used as a proxy of self-employment in Brazil. As a result of the analysis of recent self-employment s dynamics in the country, we found some similarity with the achievements observed in other nations, that are, there were reduction of self-employment, during much of the twentieth century, until the 70's, followed by a continuing growth of self-employment over the 80 s and 90 s, and a new trend raised, in the first decade of XXI century, about a new reduction of self-employment s participation in the economy. And, finally, through the analysis of some determinants of self-employment in Brazil, which are unemployment, education, age and gender, it is concluded that, generally, self-employment can be seen as a negative phenomenon in the country, tending to serve as an alternative to the worker, in the face of adverse situations found at the labor market